Three-Phase Encapsulation Platform Centered on Quercetin, Bromelain, and Eucalyptus Oil for Respiratory Support: Formulation Robustness, Gastric-Acid Protection, and Translational Evidence - Yassine, Jabar; Semenza, Gregg L.; Fuentes, Ignacio (International Journal of Public Health and Medical Research, 2026)
We evaluated a respiratory-support platform organized around quercetin, bromelain, and eucalyptus-oil-rich volatile components, and we contextualized the formulation dataset with peer-reviewed public evidence on the three signature actives. The core formulation dataset comprised three encapsulated embodiments and one direct-mix comparator from the technical dossier. The platform used three protective units: enteric-protective microspheres for bromelain, nano mixed micelles for the quercetin-centered flavonoid fraction, and sustained-release microcapsules for the eucalyptus-oil-rich volatile fraction. Across the three encapsulated embodiments, bromelain encapsulation reached 95.5%-97.2%, flavonoid encapsulation 90.8%-92.6%, and volatile-component encapsulation 92.3%-94.5%; bromelain activity retention after 2 h at pH 1.2 remained above 98.0%, while the direct-mix comparator retained only 6.8%. Total active retention after 6 months at 25 °C remained 95.8%-96.3% in the encapsulated platform versus 32.5% in the comparator. Public evidence supported the translational plausibility of the platform: quercetin attenuated smoke-induced airway inflammation and mucus production in rats; oral quercetin was safely tolerated up to 2000 mg/day in COPD patients and, in a 2025 pilot trial, reduced selected inflammatory and oxidative-stress biomarkers; 1,8-cineole showed steroid-sparing activity in severe asthma and reduced exacerbations in COPD; and oral bromelain showed tolerability and symptom improvement signals in chronic rhinosinusitis. We therefore interpret the main differentiated value of the platform as delivery-enabled robustness rather than an unsupported claim of direct clinical superiority of the full finished product.